Women's health in Canada : critical perspectives on theory and policy - Morrow, Marina Helen, 1963-; Hankivsky, Olena; Varcoe, Colleen, 1952- (University of Toronto Press, 2007)
In recent years, healthcare professionals have recognized the distinctly different healthcare needs and concerns of men and women. Women's health, in particular, has come into its own in the last two decades. In Canada, however, there has been little available in the way of a general text on women's health. This volume works toward filling that gap by providing a resource for teaching and understanding women's health in this country. To lay out the methodological and theoretical foundations for their study, editors Olena Hankivisky, Marina Morrow, and Colleen Varcoe bring together an interdisciplinary group of scholars and practitioners from economics, anthropology, sociology, nursing, political studies, women's studies, and psychology. Contributors draw on the rich history of the Canadian women's health movement, providing analysis of that history and of the emergent theory, policy, and practice. Aimed at undergraduate and graduate students as well as practitioners, the collection adopts an intersectional approach, looking closely at social factors such as gender, race, ethnicity, class, sexuality, and gender identity, and analysing how they relate both to each other and to women's health. Connections between the social, economic, and cultural contexts of women's lives and their physical, spiritual, and mental well-being are a primary focus. Providing a much needed resource for teachers, students, and practitioners of women's health in Canada, this comprehensive volume makes an important contribution to the literature.